Staphylinidae Latreille, 1803- 1802 - Majka, Christopher G.; Klimaszewski, Jan; Lauff, Randolph F. (Zenodo, 2006)
Staphylinidae Phyllodrepa floralis (Paykull) is an adventive Palearctic species found throughout Europe, north to Iceland, east to Russia, south to the Caucasus, and west through Turkey to Algeria in North Africa (Herman 2001). It is found throughout Canada from British Columbia to Newfoundland (Campbell & Davies 1991). It has previously been associated with bird and mammal nests (Steel 1970, Newton et al. 2001). In this study P. floralis was recorded only in a boreal owl nest. Hylota ochracea Casey: the genus Hylota Casey 1906 has been regarded as a synonym of Oxypoda Mannerheim 1830 (Seevers 1978) but will be reelevated to its generic status by Klimaszewski et al. (submitted). It is known from New York, Ontario, Québec, Northwest Territories (Klimaszewski et al. submitted), and Nova Scotia (C.G. Majka, unpublished data). Nothing has previously been reported about the natural history of this species, so these records, from both boreal and northern sawwhet owl nests, represent the first information about its bionomics. : Published as part of Majka, Christopher G., Klimaszewski, Jan & Lauff, Randolph F., 2006, New Coleoptera records from owl nests in Nova Scotia, Canada, pp. 33-47 in Zootaxa 1194 on page 37, DOI: 10.5281/zenodo.2646209 : {"references": ["Herman, L. H. (2001) Catalogue of the Staphylinidae (Insecta: Coleoptera): 1758 to the end of the Second Millennium. Bulletin of the American Museum of Natural History, 265. 4218 pp.", "Campbell, J. M. & Davies, A. (1991) Family Staphylinidae: rove beetles. In: Bousquet, Y. (Ed.). Checklist of Beetles of Canada and Alaska. Agriculture Canada: Research Branch, Publication 1861 / E. pp. 86 - 124", "Steel, W. O. (1970) The larvae of the genera of the Omaliinae (Coleoptera: Staphylinidae) with particular reference to the British fauna. Transactions of the Royal Society of London, 122, 1 - 47.", "Newton, A. F., Thayer, M. K., Ashe, J. S., & Chandler, D. S. (2001) Staphylinidae Latreille, 1802. In: Arnett, R. H., Jr., Thomas, M. C., Skelley, P. E. & Frank, J. H. (Eds.). American Beetles, Volume 2: Polyphaga: Scarabaeoidea through Curculionoidea. CRC Press, Boca Raton, USA. pp. 272 - 418.", "Seevers, C. H. (1978) A generic and tribal revision of the North American Aleocharinae (Coleoptera: Staphylinidae). Fieldiana Zoology, 71, i-vi + 1 - 289."]}